Libgram Assist - Jasmin, Ilani Nur Adriani; Abu, Roziya; Wan Omar, Wan Noor Faizah; Mohd Johari, Muhammad Rafi Izzuan (Universiti Teknologi MARA, Kedah, 2018)
Library is known to be boring. So what‟s next in making the modern generation break through the norm of a boring library. Digital hologram assistant which is known as LibGram Assist is the answer. LibGram Assist will help user to answer general questions just as a siri (iPhone) did. It will also deal with librarian routines when dealing with users. For instance, the LibGram Assist can be used by users to ask and also get basic information about the library. LibGram Assist will also help users by providing them the direction to find book and also around library. Other than that, LibGram Assist can also be used by handicapped users, such as blind people as they can get information through LibGram Assist easily.